Development of a guinea pig inhalational anthrax model for evaluation of post-exposure prophylaxis efficacy of anthrax vaccines. Issue 10 (28th February 2020) - Perry, Mark R.; Ionin, Boris; Barnewall, Roy E.; Vassar, Michelle L.; Reece, Joshua J.; Park, Sukjoon; Lemiale, Laurence; Skiadopoulos, Mario H.; Shearer, Jeffry D.; Savransky, Vladimir
Abstract: A next-generation anthrax vaccine candidate, AV7909, is being developed for post-exposure prophylaxis (PEP) of inhalational anthrax in combination with the recommended course of antimicrobial therapy. Clinical efficacy studies of anthrax countermeasures in humans are not ethical or feasible, therefore, licensure of AV7909 for PEP is being pursued under the US Food and Drug Administration (FDA) Animal Rule, which requires that evidence of effectiveness be demonstrated in an animal model of anthrax, where results of studies in such a model can establish reasonable likelihood of AV7909 to produce clinical benefit in humans. Initial development of a PEP model for inhalational anthrax included evaluation of post-exposure ciprofloxacin pharmacokinetics (PK), tolerability and survival in guinea pigs treated with various ciprofloxacin dosing regimens. Three times per day (TID) intraperitoneal (IP) dosing with 7.5 mg/kg of ciprofloxacin initiated 1 day following inhalational anthrax challenge and continued for 14 days was identified as a well tolerated partially curative ciprofloxacin treatment regimen. The added benefit of AV7909 vaccination was evaluated in guinea pigs given the partially curative ciprofloxacin treatment regimen. Groups of ciprofloxacin-treated guinea pigs were vaccinated. 1 and 8 days post-challenge with serial dilutions of AV7909, a 1:16 dilution of AVA, or normal saline. A group of untreated guinea pigs was included as a positive control to confirm lethal B. anthracis exposure. Post-exposure vaccination with the AV7909 anthrax vaccine candidate administered in combination with the partially curative ciprofloxacin treatment significantly increased survival of guinea pigs compared to ciprofloxacin treatment alone. These results suggest that the developed model can be useful in demonstrating added value of the vaccine for PEP.